Evaluation of TRMM 3B42 precipitation estimates of tropical cyclone rainfall using PACRAIN data. Issue 5 (12th March 2013) - Chen, Yingjun; Ebert, Elizabeth E.; Walsh, Kevin J.E.; Davidson, Noel E.
Abstract : [1] This study evaluates the latest release TRMM 3B42 version 7 (V7) estimates of daily rainfall in tropical cyclones (TCs) using the Comprehensive Pacific Rainfall Database (PACRAIN) of 24 h rain gauge observations. The evaluation is performed on two different terrain types: low‐lying atoll sites (assumed to represent open ocean conditions) and coastal and island sites (over land). The results show that TRMM 3B42 has good skill at detecting intense TC rainfall, with good correlation and pattern matching with PACRAIN observations. However, it tends to overestimate heavy rain frequency on atoll sites, but tends to underestimate heavy rain frequency on coastal and island sites. Overall, TRMM 3B42 is better able to estimate the intensity of TC heavy rain over ocean than over land. It is least skillful at coastal and island sites with high elevation, where it significantly underestimates TC heavy rainfall, suggesting that TRMM 3B42 is unable to capture orographic enhancement during TC landfall. Finally, results from V7 were compared with results from its predecessor, Version 6, showing that Version 7 of TRMM 3B42 has higher values on average for TC rain. Key Points: This study evaluates TRMM 3B42 (V7) estimates of TC rainfall over ocean. TRMM 3B42 is better able to estimate TC heavy rain over ocean than over land. TRMM 3B42 is not able to capture orographic enhancement during TC passage.